Perkembangan Desain dan Kinerja Aerator Tipe Kincir - Samsul Bahri; Radite Praeko Agus Setiawan; Wawan Hermawan; Muhammad Zairin Yunior (PERTETA, 2014)
AbstractPaddle wheel aerator widely used in aquaculture because it has the function of aeration and circulation as well as their construction is simple. However, its efficiency is not maximized so it is still expensive inoperation because of the large power consumption. Aerator performance is an important factor in the selection and use of the aerator as it relates to investment and operating cost, so the paddle wheel aeratordesign development and improvement of the performance of the operation is still possible to do. Developing of three-dimensional blade with the optimum geomerty and blade development that can move is a solution that can be done. The study aims to review the principle of aeration, performance test, evaluation criteria, and performance comparison aerator design development that have been made so as to provide an alternative to the developing of performance improvement paddle wheel aerator. This article is a summary of the ''state of the art'' design and performance of a paddle wheel aerator development.Keywords : design, aeration, paddle wheel, dissolved oxygen, efficiencyAbstrakAerator kincir banyak digunakan dalam budidaya air karena mempunyai fungsi aerasi dan sirkulasi yang baik serta kontruksinya sederhana. Namun demikian, efisiensinya belum maksimal sehingga masih mahal dalam pengoperasian karena besarnya pemakaian daya listrik. Kinerja aerator merupakan faktor penting dalam pemilihan dan penggunaan aerator karena berhubungan dengan biaya investasi dan operasional, sehingga pengembangan desain aerator kincir dan peningkatan kinerja pengoperasian masih memungkinkan untuk dilakukan. Pengembangan sudu tiga dimensi dengan geometri optimumnya dan pengembangan sudu yang dapat bergerak merupakan solusi yang dapat dilakukan. Kajian ini bertujuan menelaah kembali prinsip aerasi, uji kinerja, kriteria evaluasi, perbandingan kinerja dan perkembangan desain aerator yang sudah dilakukan sehingga dapat memberikan alternatif pengembangan guna peningkatan kinerja aerator kincir. Artikel ini merupakan rangkuman dari “state of the art” desain dan kinerja aerator kincir untuk penggunaan budidaya air.Kata kunci: desain, aerasi. kincir, kelarutan oksigen, efisiensi.Diterima: 12 November 2013; Disetujui:15 Januari 2014